Investing in agriculture to overcome the world food crisis and reduce poverty and hunger - Fan, Shenggen; Rosegrant, Mark W. (International Food Policy Research Institute, 2008)
In many parts of the world, increased agricultural growth will play a key role in addressing the current world food crisis, in contributing to overall economic growth, and in helping to achieve the first Millennium Development Goal of halving the proportion of poor and hungry people by 2015 (MDG1). The challenge of meeting MDG1 under the current circumstances is considerable, especially in Sub-Saharan Africa (SSA). Of the means used to promote agricultural growth, sound government spending can be one of the most direct and effective. This brief presents ranges of estimates of the costs involved using two different approaches. There have been numerous attempts to estimate the costs of achieving MDG1, mostly at the global or regional level, including the United Nations' Zedillo Report and studies by the World Bank and the United Nations Development Programme. These estimates have varied widely, mostly because of different methodologies, assumptions, coverage, measures, and interpretations. The two primary methodologies used in these studies have involved unit costs and growth-poverty elasticities (determining the extent to which poverty declines as growth increases). There has been no consistent basis of analysis for the first method, and studies using the second have been limited by data availability. We have attempted to address some of these issues by providing improved, research-based estimates of the global and regional investments required to achieve MDG1. Because this is a complex issue and each of the approaches mentioned above has distinct merits, we have decided to produce estimates based on both approaches to provide a fuller picture. Expanding on the two approaches, we also present estimates of the costs of financing the inputs required for accelerating agricultural production in SSA.